Effect of Employee Job Satisfaction on Organizational Citizenship Behavior at Assessment Center Indonesia - Ramadhan, Nabilah; Haizam Mohd Saudi, Mohd; ., Yenni (International Journal of Engineering and Technology, 2018)
This research was conducted to find out how much the influence of employee job satisfaction in driving the emergence of organizational citizenship behavior (OCB) on employees of the Assessment Center Indonesia (ACI). The influence is expected to create an increase in work performance and productivity in adapting to the conditions of company development and competition. The type of research used is a combination of descriptive methods and causality methods by taking a sample of 30 ACI employees. Data analysis used in hypothesis testing is simple linear regression analysis. From the results of the study, it can be concluded that the level of job satisfaction that occurs in ACI is high with a percentage of 81.17%, while the application of OCB is relatively high with a percentage of 78.48%. Job satisfaction at ACI has a positive and significant effect on OCB with an effect of 62.4%. While, the remaining influence of 37.6% is caused by other variables outside the research model.Â